2009
DOI: 10.1097/psy.0b013e3181a54341
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and Nocturnal Blood Pressure Dipping in Young Adult African Americans

Abstract: Elevated nocturnal BP may be a link between PTSD and cardiovascular morbidity in AAs that can be targeted in prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…For example, studies investigating indirect markers of sympathetic activity show that PTSD patients have higher resting heart rates and blood pressure, decreased heart rate variability, and increased plasma and urine catecholamine levels, suggesting a state of SNS overactivity (9,16). In addition, failure of blood pressure (BP) to decrease by Ն10% nocturnally (nondipping), which is thought to be mediated by SNS overactivity, is associated with increased CVD risk and is more prevalent in young AfricanAmericans with PTSD (72).…”
Section: Autonomic Dysfunction In Ptsdmentioning
confidence: 99%
“…For example, studies investigating indirect markers of sympathetic activity show that PTSD patients have higher resting heart rates and blood pressure, decreased heart rate variability, and increased plasma and urine catecholamine levels, suggesting a state of SNS overactivity (9,16). In addition, failure of blood pressure (BP) to decrease by Ն10% nocturnally (nondipping), which is thought to be mediated by SNS overactivity, is associated with increased CVD risk and is more prevalent in young AfricanAmericans with PTSD (72).…”
Section: Autonomic Dysfunction In Ptsdmentioning
confidence: 99%
“…8 On the whole, the available literature on nondipping and psychosocial variables is scarce, with results often based on small clinical samples, resulting in mixed findings. [10][11][12][13][14][15] Moreover, to our knowledge no studies have examined work-related stress in relation to nondipping in a sample of people at work.…”
Section: Introductionmentioning
confidence: 99%
“…12 On the other hand, no studies have reported on the relation between work-related stress and nondipping in a working sample. Our results clearly suggest that job strain is an independent risk factor for nondipping.…”
mentioning
confidence: 99%
“…11- 16 Only a few reports have evaluated nocturnal and early morning BP in association with mental disorders. 17 Most of the BP data reported in large-scale studies on anxiety disorder and hypertension overseas are based on measurements taken during physician check-up or at home. 11-14 Thus, few studies have investigated how psychological stress influences nocturnal BP, early morning BP and morning BP surge in patients with hypertension.…”
mentioning
confidence: 99%